ANALISIS KEPERCAYAAN PUBLIK TERHADAP KEBIJAKAN VAKSINASI COVID-19 DI KOTA SURABAYA - Arimurti Kriswibowo; Josephine Karina Putri Prameswari; Alif Galih Baskoro (Universitas Halu Oleo, 2021)
Vaccination should be one of the solutions for handling the Covid-19 outbreak, but in fact there are still many people who doubt and even don't believe it, so this creates conflict between the government and the community. The aim of this study is to determine the extent of public confidence in the Covid-19 vaccination policy made by the government so that the acceleration of handling Covid-19 can be achieved. The research method used is descriptive analysis with a quantitative approach and data collection techniques using a questionnaire. The sample in this study was taken from the population of the city of Surabaya. The sample is divided into 5 community clusters, namely students, state civil servants (ASN), health workers, education personnel and the civil society. This research is limited to an unknown sample so that the determination of the number of samples is set to be 100 respondents. The results of this study indicate that the level of public trust from the five clusters in the Covid-19 vaccination policy is in the trust category, which means that the level of public compliance with the Covid-19 vaccination policy is also high. This can be a consideration for the government to increase its efforts to build relationships with the community so that it will gain the trust of the community.